2011
DOI: 10.1371/journal.pone.0017921
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus anthracis Protease InhA Increases Blood-Brain Barrier Permeability and Contributes to Cerebral Hemorrhages

Abstract: Hemorrhagic meningitis is a fatal complication of anthrax, but its pathogenesis remains poorly understood. The present study examined the role of B. anthracis-secreted metalloprotease InhA on monolayer integrity and permeability of human brain microvasculature endothelial cells (HBMECs) which constitute the blood-brain barrier (BBB). Treatment of HBMECs with purified InhA resulted in a time-dependent decrease in trans-endothelial electrical resistance (TEER) accompanied by zonula occluden-1 (ZO-1) degradation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
43
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 40 publications
1
43
0
Order By: Relevance
“…Popov and colleagues (57) found that protease inhibitors showed a synergistic protective effect when administered with antibiotics in mice given a lethal dose of B. anthracis, suggesting that proteolytic activity contributes to the onset of anthrax. Indeed, mice infected with a B. anthracis strain lacking inhA1 survived longer than their wild-type-infected counterparts, a property potentially related to the fact that many fewer bacilli penetrate the bloodbrain barrier and infect the brain (58). The beneficial action of InhA1 does not apply just to B. anthracis; the homolog of this protease from Bacillus thuringiensis (an insect pathogen) and B. cereus (a cause of food poisoning) is necessary for efficient escape from macrophages (59).…”
Section: Discussionmentioning
confidence: 99%
“…Popov and colleagues (57) found that protease inhibitors showed a synergistic protective effect when administered with antibiotics in mice given a lethal dose of B. anthracis, suggesting that proteolytic activity contributes to the onset of anthrax. Indeed, mice infected with a B. anthracis strain lacking inhA1 survived longer than their wild-type-infected counterparts, a property potentially related to the fact that many fewer bacilli penetrate the bloodbrain barrier and infect the brain (58). The beneficial action of InhA1 does not apply just to B. anthracis; the homolog of this protease from Bacillus thuringiensis (an insect pathogen) and B. cereus (a cause of food poisoning) is necessary for efficient escape from macrophages (59).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a report that InhA cleaves the tight junction protein zonula occluden-1 and increases the permeability of human brain microvasculature endothelial cells (HBMECs) (22) suggests a role for the protease in the cerebral hemorrhaging observed in late-stage disease. Indeed, deletion of the inhA gene from the Sterne-like strain Ames 35 decreases bacterial dissemination to the blood and brain, reduces leptomeningeal hemorrhaging, and attenuates overall virulence in a mouse model of anthrax (22).…”
mentioning
confidence: 99%
“…Previous investigation of Pflughoeft (2010) suggested that the protease cascade regulated the organism response in altering environments like reacting to a changing signal or in presence of different types of tissue. Mukherjee et al (2011), also showed that NprB and Npr599 are the extracellular enzymes which interact with inhA1 and were able to degrade the plasma and matrix proteins of host. From the secretom analysis through protein-protein interaction, it has been shown that maximum acid proteases (except 2, 3, 5, 6, and 11) interacts with immune inhibitor A (inhA or othrs) as shown in Table 5.…”
Section: Discussionmentioning
confidence: 94%
“…So, in accordance to the above literature it can be concluded that protease from the organism with accession number YP_002869281.1, YP_002816538.1, YP_031148.1, EJY90308.1, EJY93035.1, EJY94285.1, AFH86425.1, AFH83987.1, ZP_05184332.1 and ZP_05183912.1 (Table 1) are extracellular in nature and they are proved to be the extracellular protein in this study through physicochemical parameter analysis. Among them zinc metalloprotease (Table 3) YP_002869281.1 (NprB), EJY94285.1 (extracellular protease) and ZP_05183912.1 (Npr599) are the part of regulatory cascade of B. anthracis which helps the cell to react against changed external environment and supports its stabilization in altered condition and may have some direct relation to the permeability of endothelial cell and degradation of plasma or matrix protein at the time of infection (Mukherjee et al, 2011). Thus the above evidence linked physicochemical parameters and PPI outputs as a result of which extracellular and intracellular acid proteases could be identified.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation